Intelligence based cadastral database selection and visualization system: concepts and prototype - Hisham, Abdullah; Bachok, Amran (2005)
The process of extracting land records information especially cadastral data for a large number of cadastral lots was tedious and time consuming. The development of Digital Cadastral Database (DCDB) by Department of Survey and Mapping Malaysia (DSMM) is one of the initiatives to shift to modern cadastral system. Least Squares adjustment approach is one of the main components in realization of Coordinated Cadastral System. Cadastral data need to be adjusted in order to verify the network closure. In order to move to a new adjustment approach, an Intelligence Based Cadastral Database selection and Visualization System should be developed. The system acts as a data provider for adjustment process. The objectives of the study are; i) to develop an intelligence based database integrity and selfcorrection mechanisms and, ii) to develop cadastral database selection and visualization system. The capabilities of the system are; executing an intelligence database integrity mechanism, generation of zones and overlapping areas also extracting cadastral information from existing DCDB. The system will automatically conducts intelligence cadastral survey concept self- checking procedures, re-compute or rebuild the cadastral records based on mathematical cadastral survey rules, preparation of corrected data input files ( DCDB and GPS) for a particular zone and reformatting of data for input into least squares adjustment software. In order to support the development of survey accurate cadastral system, object-oriented programming language approach was adopted. Prototype test bed has been executed and results show that the prototype is having a good reliability and integrity.